2013
DOI: 10.1037/a0029808
|View full text |Cite
|
Sign up to set email alerts
|

An overview of dialectical behavior therapy for professional psychologists.

Abstract: Dialectical Behavior Therapy (DBT) is a comprehensive psychosocial treatment originally designed for individuals meeting criteria for borderline personality disorder (BPD). The purpose of this article is to provide an overview of the principles and techniques of DBT for BPD, summarize current research, and discuss the implications for psychologists who wish to implement DBT. The four modes in DBT (individual therapy, skills training, as-needed consultation between sessions, and therapist consultation meetings)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 57 publications
0
70
0
1
Order By: Relevance
“…Dissociative clients present with an array of mental health problems, such as anxiety, panic and agoraphobia, obsessive-compulsive disorder (OCD), posttraumatic stress disorder (PTSD), depression, bipolar disorder, eating disorders, substance abuse, borderline personality disorder (BPD), and emotion dysregulation (Holmes et al 2005;Putnam 1989), which can be treated effectively with interventions that focus on mindfulness. Mindfulness-based interventions, including Mindfulness-Based Stress Reduction (Kabat-Zinn 1990), Mindfulness-Based Cognitive Therapy (MBCT; Segal, Williams, and Teasdale 2002), Dialectical Behavior Therapy (DBT; Linehan 1993a), and Acceptance and Commitment Therapy (ACT; Hayes, Strosahl, and Wilson 1999), have demonstrated some effectiveness in improving coping with chronic pain (Chiesa and Serretti 2011b); reducing symptoms of depression (Brown et al 2007;Chiesa and Serretti 2011a;Keng et al 2011) and major depressive episode relapses (Chiesa and Serretti 2011a;Keng et al 2011); anxiety including panic and agoraphobia, OCD, and PTSD (Keng et al 2011;Roemer and Orsillo 2009); and BPD, including inpatient hospitalization, self-injurious behavior, and suicidal ideation (Keng et al 2011;Rizvi, Steffel, and Carson-Wong 2013). Mindfulness assists in the development of the ability to regulate emotions (Arch and Craske 2006;Coffey, Hartman, and Fredrickson 2010;Farb et al 2010), tolerate distress (Coffey et al 2010), and handle interpersonal situations effectively (Block-Lerner, Adair, Plumb, Rhatigan, and Orsillo 2007;Wachs and Cordova 2007), improving mental health in cognitive, affective, and behavioral spheres (Brown et al 2007;Roemer and Orsillo 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Dissociative clients present with an array of mental health problems, such as anxiety, panic and agoraphobia, obsessive-compulsive disorder (OCD), posttraumatic stress disorder (PTSD), depression, bipolar disorder, eating disorders, substance abuse, borderline personality disorder (BPD), and emotion dysregulation (Holmes et al 2005;Putnam 1989), which can be treated effectively with interventions that focus on mindfulness. Mindfulness-based interventions, including Mindfulness-Based Stress Reduction (Kabat-Zinn 1990), Mindfulness-Based Cognitive Therapy (MBCT; Segal, Williams, and Teasdale 2002), Dialectical Behavior Therapy (DBT; Linehan 1993a), and Acceptance and Commitment Therapy (ACT; Hayes, Strosahl, and Wilson 1999), have demonstrated some effectiveness in improving coping with chronic pain (Chiesa and Serretti 2011b); reducing symptoms of depression (Brown et al 2007;Chiesa and Serretti 2011a;Keng et al 2011) and major depressive episode relapses (Chiesa and Serretti 2011a;Keng et al 2011); anxiety including panic and agoraphobia, OCD, and PTSD (Keng et al 2011;Roemer and Orsillo 2009); and BPD, including inpatient hospitalization, self-injurious behavior, and suicidal ideation (Keng et al 2011;Rizvi, Steffel, and Carson-Wong 2013). Mindfulness assists in the development of the ability to regulate emotions (Arch and Craske 2006;Coffey, Hartman, and Fredrickson 2010;Farb et al 2010), tolerate distress (Coffey et al 2010), and handle interpersonal situations effectively (Block-Lerner, Adair, Plumb, Rhatigan, and Orsillo 2007;Wachs and Cordova 2007), improving mental health in cognitive, affective, and behavioral spheres (Brown et al 2007;Roemer and Orsillo 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, dialectical behaviour therapy (DBT) is one of the best empirically supported treatments for BPD. DBT has been examined in more than a dozen randomised controlled trials (RCTs), and has been found to be superior to control conditions in reducing the primary problems it is designed to treat such as suicidal and NSSI behaviours psychiatric hospitalisations, and emergency room visits [9]. However, standard DBT does not specifically target trauma-related features or symptoms, and has only limited effects on PTSD in patients with BPD [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, following psychodynamic formulations, and based on the fact that fear of death explained half of the variance of the entire model, we suggest that psychiatrists' ability to compensate for their fear of death by curing their patients is being hampered among psychiatrists with high death anxiety, when it is activated by their frustrating encounter with BPD patients. These patients impede psychiatrists' need to compensate their own fear of death through professional achievement, by frequently creating hostility and violence, dropping out of treatment, and above allby the possibility of committing suicide (Black et al, 2011;Rizvi et al, 2013). Hence, when psychiatrists' fear of death is high, their professional impotence also increases when treating BPD, and they react to them with negative emotions.…”
Section: Discussionmentioning
confidence: 94%